Global, region and country burden of osteoarthritis at different sites in middle-aged and elderly populations from 1990 to 2021: a systematic analysis of the 2021 global burden of disease study - Huang, Guoxin; Zheng, Yiwen; Hong, Weimin; Qu, Xiaohong; Yang, Wentao; Cao, Hui; Tian, Fangtao; Lin, Hongming; Pei, Bin; Chen, Bingqian; Yang, Shu’e; Qian, Da (Frontiers in Medicine, 2025)
ObjectiveTo explore the burden and trend of osteoarthritis (OA) at different sites in middle-aged and elderly people (45 years and older) from 1990 to 2021.MethodsAge-standardized incidence rates, prevalence rates, disability-adjusted life years (Daly) rates and average annual percent change were used to quantify the disease burden and trend of OA at different sites. Decomposition analysis was conducted to explore the impact of three population-level determinants on the burden of OA and the distribution of OA burden inequality in the Socio-Demographic Index (SDI) across countries.ResultsThe age-standardized prevalence rate had increased by 8.9%, and the OA cases had increased by 2.41 times compared to 1990. The incidence and prevalence of knee, hip and hand OA decreased sequentially, while high SDI regions tended to have higher age-standardized incidence rates, prevalence rates, and Daly rates. Decomposition analysis revealed that 85.9% of the increase in OA age-standardized Daly rates was attributable to population growth. This increase was most pronounced in high SDI populations for hip OA and middle SDI populations for knee and hand OA. From 1990 to 2021, the inequality in overall OA burden between countries had decreased. The absolute inequality gap for hand OA had narrowed the most significantly (45.3%), which followed by knee OA (11.9%), while the inequality gap for hip OA has slightly increased.ConclusionIn summary, all parts of the OA burden in middle-aged and elderly people had steadily increased from 1990 to 2021, which calls to implement personalized prevention targeting different parts of OA.